Reproduction report of Garcia et al. (2023) "Experiential values are underweighted in decisions involving symbolic options" - Minho Hwang; Dongil Chung (Institute for Replication (I4R), 2025)
Classical decision theory assumes a central valuation system in which the brain encodes subjective values-or utilities-for all available options in a given choice set, regardless of how different the options are (common currency). Garcia et al. (2023) pointed out that although there has been experimental evidence for differential properties between experience-based (experiential) and description-based (symbolic) choices, the alternative possibility suggesting the existence of separate valuation systems for each modality has not been directly assessed. The authors reported empirical results supporting the alternative hypothesis that participants recruit different valuation systems for each modality. Here, we reproduced the results of this original paper and performed robustness checks. Overall, we reproduced most of the statistical results and model-based results of the original study. We employed two additional methods to test the robustness of the computational modeling used in the original study: parameterrecovery using the scripts shared by the authors and parameter estimations using different model fitting methods (maximum log-likelihood estimation (MLE) and hierarchical Bayesian estimation). Our parameter-recovery method successfully recovered most of the original model parameters, estimated from choice between experiential and symbolic values (ES phase) and between two experiential values (EE phase). Through consecutive analyses, including alternative parameter estimation methods, we confirmed that the issue does not compromise the original study's conclusions, and that all results directly related to the main conclusion (i.e., indifference points) are reproducible."
Keywords: 330